2009
DOI: 10.1007/s00024-009-0517-y
|View full text |Cite
|
Sign up to set email alerts
|

Nonplanar Faults: Mechanics of Slip and Off-fault Damage

Abstract: Stress interactions and sliding characteristics of faults with random fractal waviness in a purely elastic medium differ both qualitatively and quantitatively from those of faults with planar surfaces. With nonplanar fault models, solutions for slip diverge as resolution of the fractal features increases, and the scaling of fault slip with fault rupture dimension becomes nonlinear. We show that the nonlinear scaling of slip and divergence of solutions arise because stresses from geometric interactions at irreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
119
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(141 citation statements)
references
References 35 publications
21
119
1
Order By: Relevance
“…Self-affinity, or non-uniform scaling in shape and spatial trajectory along a geometric profile (Addison, 1997), has also been observed on natural faults and fractures over more than twelve orders of magnitude (Power et al, 1987;Power et al, 1988;Power and Tullis, 1991;Candela et al, 2011b;Renard et al, 2013). The geometry of fractal faults can be parameterized using the Hurst exponent, H, and an amplitude factor, β (e.g., Dieterich and Smith, 2009). These represent the degree of selfaffinity of the fault profile and the root mean square (rms) slope of fault elements, respectively.…”
Section: Fractal Descriptions Of 2d Fault Roughnessmentioning
confidence: 96%
See 2 more Smart Citations
“…Self-affinity, or non-uniform scaling in shape and spatial trajectory along a geometric profile (Addison, 1997), has also been observed on natural faults and fractures over more than twelve orders of magnitude (Power et al, 1987;Power et al, 1988;Power and Tullis, 1991;Candela et al, 2011b;Renard et al, 2013). The geometry of fractal faults can be parameterized using the Hurst exponent, H, and an amplitude factor, β (e.g., Dieterich and Smith, 2009). These represent the degree of selfaffinity of the fault profile and the root mean square (rms) slope of fault elements, respectively.…”
Section: Fractal Descriptions Of 2d Fault Roughnessmentioning
confidence: 96%
“…1. Dieterich and Smith (2009) assert that H = 0.5-1.0 for natural fault surfaces, and that β = 0.02-0.10 for faults on the order of L ≥ 1 km. Candela et al (2009) suggest that values of β and H can be used to characterize the amount of mechanical wear of a fault surface at various scales, with these fractal parameters used to describe the level to which asperities have been worn down and removed from a fault surface.…”
Section: Fractal Descriptions Of 2d Fault Roughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar resistance arises during the sliding of glaciers and ice sheets over rough beds [Nye, 1969[Nye, , 1970. Dieterich and Smith [2009] were the first to recognize the importance of this effect for faulting; they called it the back stress, though in this study we adopt the more specific term "roughness drag," denoted as drag . Using a two-dimensional static, linear elastic boundary element model with constant friction coefficient, Dieterich and Smith [2009] found that roughness reduces fault slip below that occurring on planar faults.…”
Section: Effects Of Roughness On Fault Mechanicsmentioning
confidence: 99%
“…Dieterich and Smith [2009] were the first to recognize the importance of this effect for faulting; they called it the back stress, though in this study we adopt the more specific term "roughness drag," denoted as drag . Using a two-dimensional static, linear elastic boundary element model with constant friction coefficient, Dieterich and Smith [2009] found that roughness reduces fault slip below that occurring on planar faults. They proposed that the otherwise ever-growing roughnessinduced stress perturbations are instead relaxed via brittle failure processes (off-fault seismicity and secondary faulting) within the off-fault material.…”
Section: Effects Of Roughness On Fault Mechanicsmentioning
confidence: 99%